PKM Meningkatkan Partisipasi Masyarakat Desa Taba Terunjam Dalam Kegiatan Musyawarah Desa - Yusuarsono, Yusuarsono; Amin, Bando; Sariningsih, Marida; Imanda, Antonio; Lorita, Evi; Handayani, Tuti; Hardandi, Hardandi; Sapruzi, Gaul (Jurnal Dehasen Untuk Negeri, 2022)
This Community Service (PKM) activity was carried out by lecturers and students of the Public Administration Study Program at Dehasen University, Bengkulu, in Taba Terunjam Village, Karang Tinggi District, Central Bengkulu Regency. The background to this activity was the low level of community participation in the Village Development Deliberation Forum (Musrenbangdes), where residents attended only around 20–30% of the invitations distributed, as well as the dominance of village officials in the decision-making process. The main objective of this activity was to increase awareness and active community involvement in democratic, transparent, and inclusive village development planning. The implementation method used a participatory approach through outreach activities, socialization, open discussions, and village deliberation simulations. The results of the activity showed a significant increase in the level of attendance and the courage of residents to express opinions, especially among youth and women. The village government also began to implement more open and participatory communication patterns. This activity demonstrated that an educational and collaborative approach between universities and the community can strengthen local democratic practices and good village governance. Thus, this PKM made a significant contribution to strengthening participatory culture and the sustainability of community-based development.